Memorandum of understanding between Universiti Teknologi MARA and University of the Immaculate Conception / Fakulti Farmasi - Universiti Teknologi MARA, Fakulti Farmasi (Universiti Teknologi MARA (UiTM), 2020)
UiTM and University of the Immaculate Conception endeavour to take necessary steps to encourage and promote cooperation.